Immigration and the U.S. Labor Market: A Look Ahead - Harry J. Holzer (Institute of Labor Economics (IZA), 2020)
The U.S. labor market will be buffeted by major changes in the next few decades, such as an aging population, automation that displaces workers and requires skill adjustments, and increases in independent or informal work and "fissured" workplaces. These forces will likely raise worker productivity over time while also raising inequality, reducing labor force participation and creating worker shortages in high-demand industries. In this context, immigration will help reduce costs in key high-demand industries (like health care and elder care), raise labor force and economic growth, and contribute somewhat to the nation's fiscal balance. Highly-educated immigrants will notably contribute to economic productivity and dynamism; but less-educated immigrants may substitute for native-born non-college workers and thereby further contribute to earnings inequality. Reforms should therefore modestly increase overall immigration over time, while shifting its composition somewhat toward more-skilled and labor-market-driven migrants. These reforms should occur within the broader context of "comprehensive" reform that also raises enforcement efforts against illegal immigrant flows while establishing a path to citizenship for the currently undocumented. These changes should also be tied to a range of efforts to raise earnings among all non-college workers.
Keywords: J1; J2; J6; 330; immigration; labor supply; labor demand; education